Espiritualidade, resiliência e logo-educação: fundamentos noológicos para o ensino religioso - Cruz, Josilene Silva da (2020)
This thesis was grounded on Viktor Frankl´s theory, especially in its anthropological aspects which includes its conception of man and its worldview. It was based on three fundamental pillars: Spirituality, Logo-Education and Resilience. These three may be respectively defined as: constitutive dimension of the human being, meaning- oriented pedagogy, and the power of spiritual resistance. The main objective of this thesis was to propose the application of Logo- Education to Religious Teaching as a pedagogical strategy that is able to provide the development of resilience out of the anthropological foundations of Viktor Frankl´s Theory, articulated with the principles stablished by the National Common Core Curriculum (NCCC). This thesis also has the following specific objectives: 01) Map out the researches that approached Victor Frankl´s theory in a post-graduation level, and use the Iramuteq software to perform an analysis of these texts, highlighting their common nucleus and some possible approximations between them; 02) List those researches performed in the field of Education that have used Frankl´s theoretical presuppositions, and highlight the interdisciplinary character of his theory in order to emphasize its common points; this is accomplished with a textual analysis also performed through the Iramuteq software; 03) Highlight the principles and applications of Logo-Education in the Brazilian context through a case study in Viktor Frankl School from Ribeirão Preto (SP); 04) Identify the interfaces between Logo-Education, the field of Religious Studies, and the Religious Teaching which is based on NCCC; showing some possible applications of Logo-Education in classroom by means of practical activities. To achieve these objectives a varied methodology was utilized, including textual analysis, case- study, and a phenomenological analysis. These studies, developed in the present thesis, demonstrated respectively the following results: 1) the applicability of Frankl´s Theory to the area of Religious Studies and Theology; 2) the intrinsic interdisciplinarity of this theoretical perspective and its applicability to the field of Education; 3) that practical applications of Logo- Education may be found, as the case-study on Viktor Frankl´s School made it clear; 4) and finally, this thesis demonstrated how the Logo-Educative approach is suitable to the kind of human formation proposed by the field of Religious Studies and thus to Religious Teaching. It was concluded that the anthropological foundations of the Frankl´s Theory can be utilized in daily school practice, especially in the curricular component of Religious Teaching, as a way of stimulating resilient postures in the students. Moreover, it was understood that this whole process might contribute to the formation of a healthier and meaningful society.